(untitled) (Journal of Student Affairs in Africa, 2021)
In this article it is argued that, through adjustment of the point of view from which history is taught and theorised in architecture schools, grand narratives of progress can be critiqued and manipulated at a structural level. This could provide more lasting transformative practices than those produced by attempts to subvert such narratives by slotting alternative details into the existing structure. The restructuring of points of view in history curricula is approached from critiques of two devices through which historical events are considered to be of objective significance: the canon and the timeline. The fundamental definitions and justifications of these devices are briefly unpacked, after which a proposal is made for alternative structures in the production of content for history and theory modules at university level. A brief description of some of the structural teaching and learning devices of studio-based design courses serves to illustrate the diversity of modes of engagement available to managers, teachers and students in the discipline. Some of those devices are then transposed onto more conventional teaching and learning structures in order to test new possibilities for history andtheory curricula. The possible outcomes of a restructuring is briefly illustrated through an example of resulting ’other timelines’ which are functional at the level of rendering history legible and comprehensible as a subject of study, but which could simultaneously move narratives of progress out of history and into the personal experience of students and tutors.